SELF-REVEALMENT IN INTERPERSONAL COMMUNICATION THROUGH SECOND ACCOUNTS ON INSTAGRAM AMONG FEMALE STUDENTS IN THE COMMUNICATION DEPARTMENT AT UNIVERSITAS ABDURRAB - Suci Shinta Lestari; Dea Syakirah; Fenny Anita (Universitas Dharmawangsa Medan, 2026)
Instagram is not only used as a means of sharing information but also as a space for self-expression. The presence of a second account has become an alternative space for female students to show a more personal side of themselves. The purpose of this study was to understand self-disclosure in interpersonal communication through a second Instagram account among Communication Science students at Abdurrab University. This study used a qualitative approach with a descriptive research type through observation, interviews, and documentation of four informants from the classes of 2022 to 2025. The results showed that female students consciously differentiate between public and private identities. The second account is used to express themselves more honestly through uploading Instagram stories and feeds containing daily activities and random things. Through the posts, female students become aware of habits, character, and emotional states. This finding is in line with the Johari Window theory, which explains that individuals have four aspects in self-disclosure: the open area, the blind area, the hidden area, and the unknown area. A limited number of followers and a predominance of close friends creates a sense of security, trust, and emotional closeness, thus encouraging interpersonal communication through direct messages, comments, and likes. Despite greater freedom, female students remain cautious about self-disclosure due to the potential for content to be disseminated through screenshots. This suggests that self-disclosure is selective and serves as a means of negotiating between self-expression and the boundaries of privacy.